CHINA IN CENTRAL ASIA: ENERGY INTERESTS AND ENERGY POLICY - PARAMONOV, Vladimir; STROKOV, Alexey (CENTRAL ASIA AND THE CAUCASUS, 2010)
In the mid-1990s, China displayed the first flickers of interest in the Central Asian fuel and energy complex, which has been steadily growing since that time along with Beijing’s interest in other spheres of the region’s economy. In the latter half of the last decade of the 20th century, the project activities of China and Chinese companies in the Central Asian energy segment were concentrated in Kazakhstan’s oil and gas sector. In the early 21st century, however, this interest began gradually spreading to the rest of the region to become diversified by the industry’s branches. Today, China is showing a lot of interest in the oil and gas of Kazakhstan and Turkmenistan and in the nuclear power production of the former. China is paying enough attention to the fuel and energy complexes of the rest of the region to promote its economic and political interests in each of the states and the region as a whole.